2011
DOI: 10.4269/ajtmh.2011.10-0739
|View full text |Cite
|
Sign up to set email alerts
|

West Nile Virus Vector Competency of Culex quinquefasciatus Mosquitoes in the Galápagos Islands

Abstract: Abstract. The mosquito-transmitted pathogen West Nile virus (WNV) is not yet present in the Galápagos Archipelago of Ecuador. However, concern exists for fragile endemic island fauna after population decreases in several North American bird species and pathology in certain reptiles. We examined WNV vector competency of a Galápagos strain of mosquito ( Culex quinquefasciatus Say). Field specimens were tested for their capacity to transmit the WN02-1956 strain of WNV after incubation at 27°C or 30°C. Rates of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 54 publications
1
33
0
1
Order By: Relevance
“…The EIP obtained in this study was longer than the one reported previously because the dissemination and transmission occurred at Day 15 post-feeding in our experiments, whereas dissemination was obtained earlier at Day 5 and transmission at Day 7, post-feeding during a vector competence analysis of Culex pipiens using NY99 strain. 27,59 Furthermore, based on our data and the daily survival rate obtained in earlier studies, the estimated survival of infective life rate ranged from (0.871) 15 and (0.883). 15,63 In other words, only 12.59 to 15.46% of the populations of Culex quinquefasciatus will survive up to Day 15 postinfection, which is the time needed from infection to transmission.…”
Section: Vector Competence Of Culex For West Nile Virus Lineagesmentioning
confidence: 52%
See 1 more Smart Citation
“…The EIP obtained in this study was longer than the one reported previously because the dissemination and transmission occurred at Day 15 post-feeding in our experiments, whereas dissemination was obtained earlier at Day 5 and transmission at Day 7, post-feeding during a vector competence analysis of Culex pipiens using NY99 strain. 27,59 Furthermore, based on our data and the daily survival rate obtained in earlier studies, the estimated survival of infective life rate ranged from (0.871) 15 and (0.883). 15,63 In other words, only 12.59 to 15.46% of the populations of Culex quinquefasciatus will survive up to Day 15 postinfection, which is the time needed from infection to transmission.…”
Section: Vector Competence Of Culex For West Nile Virus Lineagesmentioning
confidence: 52%
“…quinquefasciatus exhibited an infection rate of 39-55% using a titer of 10 7 pfu/mL, which is comparable to or lower than the rates obtained in this study. 59 Concerning the lineages 2 and Koutango, Cx. quinquefasciatus, exhibited no or low susceptibility, respectively, whereas Cx.…”
Section: Discussionmentioning
confidence: 99%
“…Paull & Johnson (2013) summarize the complex physiological, range-shift, biotic-interaction and evolutionary challenges of predicting and attributing climate-driven changes to disease dynamics. However, a substantial body of publications and health-agency reports highlights the significance of climate change on vector-borne diseases (Kurane, 2010;Eastwood et al, 2011;Guis et al, 2012;Gallana et al, change. In the context of mosquito research, many zoos have the potential to provide valuable mosquito-monitoring and research opportunities This is largely due to the combination of novel species assemblages that zoos and similar facilities maintain, and the diverse range of microhabitats and shelters suitable for mosquito breeding and overwintering (Adler et al, 2011;Nelder, 2007;Tuten, 2011a;Tuten 2011b;Tuten et al, 2012).…”
Section: Mosquito Spatio-temporal Changes and Associated Health Issuesmentioning
confidence: 99%
“…Paull & Johnson (2013) summarize the complex physiological, range-shift, biotic-interaction and evolutionary challenges of predicting and attributing climate-driven changes to disease dynamics. However, a substantial body of publications and health-agency reports highlights the significance of climate change on vector-borne diseases (Kurane, 2010;Eastwood et al, 2011;Guis et al, 2012;Gallana et al, 2013; World Health Organization, 2013b), including actual and projected spatio-temporal changes to mosquito distribution and associated disease issues (Patz et al, 2005;Confalonieri et al, 2007;Paaijmans et al, 2010;Garamszegi, 2011;Roiz et al, 2011;Hongoh et al, 2012;Loiseau et al, 2012;Altizer et al, 2013;Fischer et al, 2013;Gallana et al, 2013;Hueffer et al, 2013; World Health Organization, 2013c). …”
mentioning
confidence: 99%
“…The archipelago, famous for its unique range of endemic fauna and flora which has evolved in isolation over millennia, is recognised as a United Nations Education Scientific and Cultural Organisation [UNESCO] World Heritage site1 and generates considerable economic income for Ecuador through ecotourism. However, as increasing connectivity with the continental Americas, primarily driven by a rapidly expanding tourism industry and growing human population, diminish geographic barriers, the Galápagos ecosystem is threatened by invasive species and novel pathogens234. Here we quantify epidemiological factors key to the establishment and transmission of West Nile virus [WNV] should this mosquito-borne virus be introduced to Galápagos, focusing on Aedes taeniorhynchus , a native species and the most abundant and widely-distributed mosquito on the islands5.…”
mentioning
confidence: 99%